Immune-Related Nine-MicroRNA Signature for Predicting the Prognosis of Gastric Cancer - Xu, Jingxuan; Wen, Jian; Li, Shuangquan; Shen, Xian; You, Tao; Huang, Yingpeng; Xu, Chongyong; Zhao, Yaping (Frontiers in Genetics, 2021)
Current studies have demonstrated the superiority and utility of microRNAs (miRNAs) as new biomarkers for cancer diagnosis, therapy, and prognosis. In the current study, to explore the prognostic value of immune-related miRNAs in gastric cancer (GC), we analyzed miRNA expression profiles in 389 GC patients from the Cancer Genome Atlas project. With the use of forward and backward variable selection and multivariate Cox regression analyses model, we confirmed nine miRNAs (ImmiRSig) (miR-125b-5p, miR-99a-3p, miR-145-3p, miR-328-3p, miR-133a-5p, miR-1292-5p, miR-675-3p, miR-92b-5p, and miR-942-3p) in the training cohort proving a capability to divide patients into high- and low-risk groups with significantly different survival. In an independent test cohort of 193 GC patients, ImmiRSig has been successfully validated. Univariate and multivariate Cox regression analyses indicated that ImmiRSig was an independent prognostic factor after adjusting for other clinical covariates. The identified ImmiRSig has significant clinical importance for further prospective validation that improves outcome prediction and guides personalized treatment for patients with GC. Finally, a significant association between the ImmiRSig and the half maximal inhibitory concentration was observed, suggesting that ImmiRSig may predict the clinical efficacy of chemotherapy.